Enantioselective "clip-cycle" synthesis of di-, tri- and spiro-substituted tetrahydropyrans. Issue 6 (19th January 2022) - Alomari, Khadra; Sai Pavan Chakravarthy, N.; Duchadeau, Bastien; Ermanis, Kristaps; Clarke, Paul A.
Abstract : ω-Unsaturated alcohols were "clipped" via alkene metathesis to a thioester activating group, which was followed by a chiral phosphoric acid catalyzed intramolecular oxa-Michael cyclization to yield tetrahydropyrans with excellent enantioselectivity. Abstract : ω-Unsaturated alcohols were "clipped" via alkene metathesis to a thioester activating group, which was followed by a chiral phosphoric acid catalyzed intramolecular oxa-Michael cyclization to yield tetrahydropyrans and spiro-tetrahydropyrans with excellent enantioselectivity. The mechanism and origin of the enantioselectivity was probed by DFT calculations and kinetic isotope studies, where there was excellent correlation between the computational and synthetic investigations.